MENINGKATKAN KEMAMPUAN KOMUNIKASI LISAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Hisnan Hajron, Kun (Dharmas Education Journal (DE_Journal), 2024)
This study aims to improve oral communication skills using the jigsaw type cooperative learning model. Indicators of oral communication skills include being able to listen, convey messages clearly and the interlocutor can understand the message conveyed with a measuring tool in the form of observation. The steps of implementing jigsaw include providing an explanation of the scope of the material content, dividing students into several small groups called the original group, then asking students to gather into several new groups called expert groups to explore certain material content, then returning to the initial group to share information obtained in the expert group. The research subjects totaled 96 people with the material content provided was related to the theory of Multiple Intelligences. The research method used Classroom Action Research (PTK) with a cyclical process of planning, action, observation, and reflection with a total of 2 cycles. The results found were an increase in the number of good categories in all indicators and a drastic decrease in the category of less in the three indicators. Thus, it can be concluded that the application of the jigsaw type cooperative learning model can improve oral communication skills.